Analysis of the Quality of Services for the Issuance of Land Certificates at the National Land Agency of West Aceh Regency - Syarifah Yuni Fadilla; Najamuddin Najamuddin (Publica: Jurnal Pemikiran Administrasi Negara, 2022)
This article aims to determine the extent to which the National Land Agency (BPN) of West Aceh in providing quality services in making land certificates, this study uses a qualitative research design with a descriptive approach. Researchers in this study found that the quality of service was still below standard in terms of making land certification documents at the Aceh Barat district government office. This can be seen through the five indicators of Lovelock's theory (2011): tangible evidence, reliability, responsiveness, assurance, and empathy. Data processing delays, insufficient number of staff, unclear instructions for obtaining land titling, and frequent complaints from the public about service delays are all problems that have emerged so far. The land office held socialization for the making of land certificates due to the lack of a special queue number collection tool for making counters and the lack of LARASITA cars for socialization. Because there are still many uncertified lands in West Aceh district. Communities are reluctant to register land because they believe the process will take a long time and is unclear if it is not completed on time, according to a schedule that is announced to the public.